1991
DOI: 10.1002/pc.750120108
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of interfacial shear strength on matrix and interphase properties

Abstract: Experiments were conducted to determine the dependence of the interfacial shear strength on the bulk material matrix properties using model compounds based on epoxy/amine chemistry. AS4, carbon fibers were used as the subject for these measurements with both a difunctional epoxy (DGEBA) system as well as a tetrafunctional epoxy (MY720) system. Amine curing agents were carefully chosen to produce matrices which produced a range of matrix properties from brittle, elastic to ductile, plastic. The fiber-matrix int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Rosen [20], Cox [21], and Whitney and Drzal [22] have shown that the square root of the shear modulus of the matrix appears explicitly in any model of the interfacial shear strength. It has been demonstrated experimentally [23,24] that the fiber-matrix interfacial shear strength has a dependence on both the product of the strain-to-failure of the matrix times the square root of the shear modulus and on the difference between the test temperature and Tg when the interfacial chemistry is held constant.…”
Section: Fiber-matrix Adhesion and The Interphasementioning
confidence: 99%
“…Rosen [20], Cox [21], and Whitney and Drzal [22] have shown that the square root of the shear modulus of the matrix appears explicitly in any model of the interfacial shear strength. It has been demonstrated experimentally [23,24] that the fiber-matrix interfacial shear strength has a dependence on both the product of the strain-to-failure of the matrix times the square root of the shear modulus and on the difference between the test temperature and Tg when the interfacial chemistry is held constant.…”
Section: Fiber-matrix Adhesion and The Interphasementioning
confidence: 99%
“…The interphase is the region between the surface of the reinforcement and the polymer matrix where the chemistry is di erent from that of the bulk matrix (Drzal, 1990;Rao and Drzal, 1991;Madhuka and Drzal, 1991). The mechanical properties in the interphase are a direct re ection of the interphase chemistry.…”
Section: Introductionmentioning
confidence: 97%
“…It is to be pointed out that in their analysis Skourlis & McCullough take care to say that 'no major interfacial debonding appears even up to the saturation point'. Rao & Drzal (1991), who also derived a quasi-elastic model, do the same when they specify that the comparisons of systems are of value only if 'all other things (are) equal'.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration was given as early as 1978 for glass fibres in epoxy or polyester resins tested up to 100-120 ЊC by Ohsawa et al (1978) who concluded that 'if the interfacial strength is greater than the matrix shear strength, the apparent strength calculated from the fragmentation test is merely the matrix shear strength'. Other authors conducted fragmentation tests on the (necessarily) same limited range of temperatures with glass (DiBenedetto & Lex, 1989;DiBenedetto, 1991) or carbon fibres (Wimolkiatisak & Bell, 1989;Skourlis & McCullough, 1993;Detassis et al, 1995) or with resin mixtures of variable stiffness associated with carbon (Rao & Drzal, 1991) or Nicalon SiC fibres (Ho et al, 1995); they all observed an increase of the fragment length with temperature or the reduction of the matrix modulus. In the last two studies, the authors point out that the extension of the fibre/matrix debonding process does not change very much from one resin system to the other and thus the comparison of the elastic reloading modes is quite relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation